Analysis, design and evaluation of man-machine systems : proceedings of the IFAC/IFIP/IFORS/IEA conference, Baden-Baden, Federal Republic of Germany, 27-29 September 1982 - Johannsen, Gunnar; Rijnsdorp, John E. (IFAC proceedings series., 1983)
Analysis, Design, & Evaluation of Man-Machine Systems presents an examination of the construction and application of a combined network and production systems model. It discusses the computer simulation and experimental results of a fuzzy model of driver behavior. It addresses the ergonomic aspects of working places in control rooms.